Perspectives of health professionals on the best care settings for pediatric trauma casualties: a qualitative study - Raya Madar; Bruria Adini; David Greenberg; Yehezkel Waisman; Avishay Goldberg (BMC, 2018)
Abstract Background Critically-injured children are frequently treated by providers who lack specialty pediatric training in facilities that have not been modified for the care of children. We set out to understand the attitudes and perspectives of policy makers, and senior nursing and medical managers in the Israeli healthcare system, concerning the provision of medical care to pediatric trauma casualties in emergency departments. Methods We conducted semi-structured interviews with 17 health professionals from medical centers across Israel and the Ministry of Health. The interviews were analyzed by qualitative methods. Results There was lack of clarity and uniformity concerning the definition of a pediatric trauma casualty. All of the participants attributed extreme importance to the professional level of the care team manager, and most suggested that this should be a pediatric emergency medicine specialist. They emphasized the importance of around-the-clock availability of pediatric medical teams to care for young trauma casualties, and the crucial need for caregivers to be equipped with a wide variety of professional skills for the adequate treatment of a broad spectrum of injuries. All participants described significant variability in pediatric-care training and experience among physicians and nurses working in emergency departments. Most participants believe that pediatric trauma casualties should be treated in designated pediatric emergency departments, in a limited number of medical centers across the country. Conclusions Our findings indicate that specialized pediatric EDs would constitute the best location for intake of children with major traumatic injuries. Pediatric emergency medicine specialists should manage trauma cases using pediatric surgeons as ad-hoc consultants. The term 'pediatric patient' should be defined to allow trauma patients to be referred to the most appropriate ED. Teams working at these EDs should undergo specialized pediatric emergency medicine training. Finally, to regulate the key aspects of trauma care, clear statutory guidelines should be formulated at national and local levels.